1964
DOI: 10.1113/jphysiol.1964.sp007521
|View full text |Cite
|
Sign up to set email alerts
|

Direct nervous pathways between the cervical vagus and the aortic or superior laryngeal nerves traversed by baroreceptor, ‘pulmonary stretch’, and other fibres in the cat

Abstract: Only brief reports have appeared concerning carotid sinus baroreceptor fibres which conduct orthodromic impulses peripherally in the aortic nerve (Holmes, 1954;Bianconi & Raschi, 1959) and a vagal cardiac branch (Green, 1959) of the cat. The finding of a similar fibre in the cervical vagus of a dog (Jewett, 1964) led to the study to be described here. In the cat, besides these fibres, other baroreceptor fibres and some 'pulmonary stretch' fibres were found to conduct impulses peripherally in the aortic nerve. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the absence of more detailed study it is suggested that the results with group IV fibres and some of the unclassified fibres are consistent with the suggestion by Jewett (1964b) that there is a system of afferent nerves having collateral branches and/or peripheral synaptic connexions. The ones described here would have unknown efferent actions on the lungs and trachea.…”
Section: Group IV Vagal and Sympathetic Fibres; Other Fibresmentioning
confidence: 54%
See 1 more Smart Citation
“…In the absence of more detailed study it is suggested that the results with group IV fibres and some of the unclassified fibres are consistent with the suggestion by Jewett (1964b) that there is a system of afferent nerves having collateral branches and/or peripheral synaptic connexions. The ones described here would have unknown efferent actions on the lungs and trachea.…”
Section: Group IV Vagal and Sympathetic Fibres; Other Fibresmentioning
confidence: 54%
“…The behaviour of group IV fibres was so characteristic of vascular afferent nerves (baroreceptor fibres), that it was most surprising to find that activity was often abolished by block of cervical vagal conduction. The patterns of response to various stimuli which changed blood pressure showed clearly that the fibres were not coming from systemic arterial baroreceptors, which may possibly send fibres down the vagus nerves (Holmes, 1954;Bianconi & Raschi, 1959;Green, 1959;Jewett, 1964b), and the activity could usually be correlated best with central venous or atrial pressures, although this was not established. The timing in relation to the cardiac cycle, the usual inspiratory increases in frequency, the changes on lung inflation by positive pressure (augmentation of discharge 85 J. G. WIDDICOMBE for the pulmonary fibre in an open-chested dog, and inhibition in closedchested animals), and the responses to tracheal occlusion, are all consistent with most of the fibres arising from receptors on the low-pressure vascular compartments of the chest.…”
Section: Group IV Vagal and Sympathetic Fibres; Other Fibresmentioning
confidence: 99%
“…This suggests that the fibres may become smaller as they descend, which might explain the difficulties in demonstrating histologically that there are myelinated efferent fibres in the vagal cardiac branches (Heinbecker, 1931;Heinbecker & O'Leary, 1933;Daly & Evans, 1953;Evans & Murray, 1954;Mizeres, 1955Mizeres, , 1957Agostoni, Chinnock, Daly & Murray, 1957). Type I fibres are probably not the same as those reported by Okada et al (1961b) since two Type I fibres were not affected by superior vena caval infusions; furthermore, there is a possibility that the fibres reported by these authors are not cardio-inhibitory (see Jewett, 1964).…”
Section: Discussionmentioning
confidence: 74%
“…One Type I fibre had a higher conduction velocity inthe proximal vagus than in the distal vagus, which has been reported for some single fibres in the vagus nerve (Iggo, 1958;Paintal, 1962). This suggests that the fibres may become smaller as they descend, which might explain the difficulties in demonstrating histologically that there are myelinated efferent fibres in the vagal cardiac branches (Heinbecker, 1931;Heinbecker & O'Leary, 1933;Daly & Evans, 1953;Evans & Murray, 1954;Mizeres, 1955Mizeres, , 1957Agostoni, Chinnock, Daly & Murray, 1957 Jewett, 1964).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation